Mucinous subtype as prognostic factor in colorectal cancer: a systematic review and meta-analysis. Issue 5 (18th January 2012) - Verhulst, J; Ferdinande, L; Demetter, P; Ceelen, W
Abstract : Background: Mucinous adenocarcinoma (MAC) of the colorectum has been known and studied for many years. The prognostic significance of this histological subtype remains controversial. The authors reviewed the prognostic significance of mucinous differentiation in colorectal cancer. Materials and methods: A systematic web-based search was performed using Web of Knowledge and Medline. Articles published in English, German or French which used the WHO definition of MAC and described cohort studies, case–control studies or cross-sectional studies comparing survival in patients with MAC and adenocarcinoma (AC) not otherwise specified were included. Data on first author, year of publication, country, number of patients included, prevalence of MAC, % stage IV disease, % disease located in the proximal colon, mean age at presentation, % male patients and 5-year overall survival were extracted from individual studies. A fixed-effects meta-analysis model was used for analysis. The primary outcome was survival, expressed as the HR. Differences between categorical outcome parameters were quantified using the RR and corresponding 95% CI. Results: 44 studies and 222 256 patients were included. The RR for proximal disease versus distal disease was 1.55 (95% CI 1.53 to 1.58). Mucinous differentiation was less frequent in male subjects (RR 0.93 (95% CI 0.91 to 0.94)). Interestingly, the prevalence of stage IV disease was similar in MAC and AC (RR 0.99 (95% CI 0.96 to 1.02)). Thirty-five articles were included in the survival analysis. A worse survival in MAC versus AC was demonstrated (HR 1.05 (95% CI 1.02 to 1.08)). Conversely, three out of four studies reported a better survival in MAC with microsatellite instability (MSI). Due to heterogeneity a meta-analysis on the effect of MSI was not possible. Conclusion: MAC more often originates from the right colon and is less frequent in male subjects. The authors did not identify a difference in the proportion of stage IV patients at presentation. Mucinous differentiation results in a 2–8% increased hazard of death, which persists after correction for stage. More research is needed to define the interaction between mucinous differentiation, MSI and outcome.